Green procurement in construction industry: a theoretical perspective of enablers and barriers - M., Waris; Ng, Hwee Ting; Lee, Chia Kuang; Mohd Ridzuan, Darun; Mohd Faris, Khamidi (EDP Sciences, 2018)
The global environment is gradually deteriorating and the construction sector is commonly considered as most influential to such issues extending from non-renewable resource depletion to global warming. Developing countries in Asia produce more than 60% of the CO2 emissions and this increases from year to year in the real estate industries. Traditional building materials experience low environmental performance; furthermore, they can lead to several risks related to the environment which consists of the construction process and building operation, such as the diverse emission of hazardous waste. Therefore, green procurement has been considered as a gateway approach for enhancing the environmental performance in the building industry. Since the procurement phase is the early stage of the project lifecycle, it is the most noteworthy to ensure a sustainable future perspective. Therefore, this paper intends to establish a theoretical outlook to exploit the enablers and barriers for promoting green procurement in the construction industry.